The ABC of crop insurance: Farmers training report - Osiemo, Jamleck; Templer, Noel; Muriithi, Cyrus; Kinyua, Ivy Wambui; Karobia, Priscilla (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report focuses on a training program in Meru County that educated farmers about crop insurance. It covered the basics of insurance, its benefits, and how it works, including aspects like basis risk, premiums, and claims.